Hypertrophic cardiomyopathy occurred after successful surgical correction of supravalvular aortic stenosis: a case report of Williams–Beuren syndrome - Yu, Hongxiao; Ruan, Yang; Sun, Manfang; Li, Taole; Nie, Zhihua (Frontiers in Pediatrics, 2025)
Williams–Beuren syndrome (WBS) is a multisystemic disorder caused by a microdeletion on chromosome 7q11.23.The supravalvular aortic stenosis (SVAS) is the most prevalent cardiovascular complication of WBS. However, hypertrophic cardiomyopathy (HCM) has rarely been reported in this population. We present a case of a patient with WBS who underwent successful surgical repair for SVAS in infancy but later developed HCM. Comprehensive genetic testing and further bioinformatic analysis revealed a deletion of approximately 1,486 kb at the 7q11.23 locus, and subsequent echocardiography demonstrated characteristic features of HCM. This case highlights the rare but clinically significant association between WBS and HCM, providing a foundation for further investigation into the biological mechanisms or potential biomarkers for HCM in WBS patients.